APLIKASI PENENTUAN PARAMETER TRANSFORMASI LOKAL BATU HIJAU UNTUK SURVEI DAN PEMETAAN AREA TAMBANG PT. NEWMONT NUSA TENGGARA - Bambang Darmo Yuwono; Amin Marzuki (Diponegoro University, 2010)
Most of mining technical activities, especially survey and mapping use local reference system, including inmining area Batu Hijau of PT Newmont Nusa Tenggara. While the data obtained by using GPS measurement,it should be transform from global coordinate system to local coordinatesystem.The process needstransformation parameters to do coordinate transformation. The object of this research is to build anapplication in determining transformation parameters from global system to local system and analyzeparameters of Batu Hijau of PT Newmont Nusa Tenggara. These transformation parameters are then expectedto be used for determining coordinate in local reference. The result can be obtained the most appropriate localparameters of Batu Hijau for surveying and mapping with geometric transformation accuracy.For this reaserch Melodensky Badekas 3D relatively better than Bursa Wolf 3D appropriate geometricaccuracy are SD 0.0919 m; RMSE 0.0322 m for the Melodensky Badekas and SD 0.2506 m; RMSE 0.0322 mfor the Bursa Wolf. Affine 2D relatively better than Helmert 2D are SD 0.3082 m; RMSE 0.0931 m for Affine2D and SD 0.3531 m; RMSE 0.1070 m for the Helmert 2D.